Persistent Hiccups as the Only Presenting Symptom of ST Elevation Myocardial Infarction - Nasreen Shaikh; Rishi Raj; Srinivas Movva; Charles Mattina (Case Reports in Cardiology)
Clinical manifestations of acute myocardial infarction can be more than just chest pain. Patients can present with dyspnea, fatigue, heart burn, diaphoresis, syncope, and abdominal pain to name a few. Our patient was a 74-year-old male with a past medical history of type 2 diabetes mellitus, hypertension, hyperlipidemia, and COPD due to chronic tobacco use, who presented with persistent hiccups for 4 days and no other complaints. Coincidently, he was found to have a diabetic foot ulcer with sepsis and acute kidney injury and hence was admitted to the hospital. A routine 12-lead EKG was done, and he was found to have an inferior wall ST elevation myocardial infarction. He underwent diagnostic catheterization which demonstrated 100% right coronary artery occlusion and a thallium viability study which confirmed nonviable myocardium; hence, he did not undergo percutaneous coronary intervention. Elderly patients who present with persistent hiccups should be investigated for an underlying cardiac etiology.